The Role of Leadership, Work Motivation and Organizational Commitment to Hospital Performance in Bali - Suwandana, I Gusti Made (Journal of World Science, 2024)
The research aims to understand the influence of leadership, work motivation, and organizational commitment on employee performance in hospitals in Bali. The method employed in this study is a quantitative approach. A total of 200 respondents, who are hospital employees in Denpasar, Bali, were sampled. Data collection was conducted through interviews and questionnaires. The analysis technique used was multiple linear regression. The research results indicate a positive and significant relationship between leadership, work motivation, and employee commitment with the performance of hospital employees in Denpasar. In other words, the better the leadership style applied by the leaders, the higher the work motivation, and the higher the employee commitment to the company, the better the performance of hospital employees. This highlights the importance of these factors in creating a productive work environment and motivating employees to contribute maximally. By paying attention to and improving these aspects, hospitals can enhance operational effectiveness and service delivery. The implications of the research include obtaining and utilizing leadership, motivation, commitment, and employee performance indicators as part of the company's strategy.